(untitled) (Eurasian Medical Research Periodical, 2022)
Toxoplasma gondii causes toxoplasmosis, an infectious illness. T. A parasite called gondii may infect practically any warm-blooded animal. mammal and is widespread across the world, but The only known definite hosts where it may sexually reproduce are domestic cats.. One of the most widespread parasites in humans is T. gondii. industrialized nations that affects people. People who lack mannose-binding lectins are susceptible to upper respiratory infections as well as infections of other bodily systems. People who have this illness run the risk of developing more severe infections including meningitis and pneumonia. The frequency and intensity of an illness’s symptoms varies depending on the type of infection. This study aims to review the association between the susceptibility of infection with Toxoplasma and variation in MBL gene